2015
DOI: 10.1016/j.jana.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding HIV Testing Behaviors of Minority Adolescents: A Health Behavior Model Analysis

Abstract: Adolescents and young adults are the fastest-growing age group of people living with HIVinfection in the United States. Yet many adolescents and young adults with high-risk behaviors for HIV are unaware of their HIV status and have never had an HIV test. The purpose of our work was to understand minority adolescents’ beliefs, attitudes, and behaviors related to HIV testing. We conducted focus group sessions with 41 minority adolescents to assess their perceptions about HIV testing. We triangulated the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
(31 reference statements)
4
14
0
2
Order By: Relevance
“…Our findings about knowledge of HIV testing support common findings that most youth know about HIV testing, where to get tested, and have been tested at least once in their life, but don‘t get tested frequently enough due to misperceptions of risk and barriers such as social stigma and economic limitations (28). We used 2 questionnaires to measures knowledge and each had a scale of 0 (none correct) to 18 (perfect score).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings about knowledge of HIV testing support common findings that most youth know about HIV testing, where to get tested, and have been tested at least once in their life, but don‘t get tested frequently enough due to misperceptions of risk and barriers such as social stigma and economic limitations (28). We used 2 questionnaires to measures knowledge and each had a scale of 0 (none correct) to 18 (perfect score).…”
Section: Resultssupporting
confidence: 83%
“…Peer influence and perceived social norms have been identified as highly influential factors that motivate people to get tested for HIV, along with a history of sexually transmitted infection and risk awareness (8, 28). Our findings on youths‘ motivations to use the HIVST confirm existing research.…”
Section: Resultsmentioning
confidence: 99%
“…The HIV self-test may be of particular relevance to adolescents and young adults who are less likely to use clinic-based testing services because of coverage, stigma, and other priorities (8). Ethnic minority youth face significant challenges accessing preventive and treatment services (9-12).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of the decision to obtain an HIV test was grounded in the knowledge as well as young adult's ability to assess HIV risks from sexual behaviors and identify the benefits of testing; this was observed in the majority of participants in this study and noted by previous studies (Leonard, Rajan, Gwadz, & Aregbesola, 2014;Meadowbrooke et al, 2014;Schnall, Rojas, & Travers, 2015). In this study, there were also no specific demographic differences in the participants that identified HIV risks and testing benefits, which may be an indication of the importance of these attributes in the decisionmaking process of young adults regardless of demographic characteristics.…”
Section: Scheduled Hiv Testingmentioning
confidence: 66%
“…Our research uniquely identified participants' self‐convincing process as they initiated the decision to seek testing. The participants who identified this prompt were relatively younger and may experience mental testing barriers like stigma and fear that remain deterrents of HIV testing (Phillips, Ybarra, Prescott, Parsons, & Mustanski, 2015; Schnall et al, 2015; Strauss, Rhodes, & George, 2015). Hence, the ability to assuage feelings of concern with the knowledge of HIV testing benefits through self‐convincing was essential for young adults to initiate testing decisions.…”
Section: Discussionmentioning
confidence: 99%